End of empire 100 days in 1945 that changed Asia and the world - Chandler, David P. (David Porter) 1933-; Cribb, R. B.; Narangoa, Li (Asia insights, 2016)
Charts 100 days of dreams, drama and turmoil across eastern Asia at the end of World War II. Combines daily events with commentary, photographs, maps and personal accounts. Part of a radically new multi-layered, 'real-time' publication commemorating events 70 years after they happened and 'broadcast' day by day.